Methods in historical corpus pragmatics: epistemic stance in early modern English - Landert, Daniela (Studies in English language, 2024)
"Drawing on an extensive corpus-based study, this book explores theoretical and empirical discussions of stance research applied to data from Early Modern English. It also presents a new method for the study of pragmatic phenomena, making it essential reading for researchers and students in both historical pragmatics and corpus pragmatics"--